Необхідність удосконалення системи адміністрування податків та зборів - Линник, Олена Іванівна; Анісімова, Є. В. (НТУ "ХПІ", 2010)
The problems of administration of taxes are considered in the article. Faults of the state tax policy during reforming economy are shown. The ways of improvement of the control mechanism to tax system of Ukraine are offered.
Keywords: політика податкова; система податкова; реформування економіки; регулювання